Correlation of Patience in Overcoming Bipolar Disorder Muhammad Quraish Shihab's Perspective in Q. S. Al-Baqarah Verse 155 - Innisa, Ismu Nanda; Andy, Safria; Is, Fadhilah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
A bad environment will shape the bad character of a person's character. This is where all forms of good attitudes, words, and habits carried out in the environment will form a person's mental health. The application of religion can be one that can be applied in the environment to get good habits. This will be a factor that helps children to fortify themselves from bad responses when facing exams. Likewise, a bad environment will form a bad mentality in children. So that this mental disorder triggers the emergence of bipolar disorder. This study aims to determine the relevance of good practices and the application of tasawuf akhlaqi in maintaining mental health so that it will prevent bipolar disorder in a person. The approach taken in this research is qualitative with the type of library research, in which the related data will be analyzed to get the desired results. The results of this study indicate that presenting religious concepts in life can lead to patience in facing trials, and the emotions that will be caused can be managed properly.